Implementation of a quality improvement initiative in Belgian diabetic foot clinics: feasibility and initial results. Issue 5 (July 2014) - Doggen, Kris; Van Acker, Kristien; Beele, Hilde; Dumont, Isabelle; Félix, Patricia; Lauwers, Patrick; Lavens, Astrid; Matricali, Giovanni A.; Randon, Caren; Weber, Eric; Van Casteren, Viviane; Nobels, Frank; et al.
Abstract Background This article aims to describe the implementation and initial results of an audit–feedback quality improvement initiative in Belgian diabetic foot clinics. Methods Using self‐developed software and questionnaires, diabetic foot clinics collected data in 2005, 2008 and 2011, covering characteristics, history and ulcer severity, management and outcome of the first 52 patients presenting with a Wagner grade ≥2 diabetic foot ulcer or acute neuropathic osteoarthropathy that year. Quality improvement was encouraged by meetings and by anonymous benchmarking of diabetic foot clinics. Results The first audit–feedback cycle was a pilot study. Subsequent audits, with a modified methodology, had increasing rates of participation and data completeness. Over 85% of diabetic foot clinics participated and 3372 unique patients were sampled between 2005 and 2011 (3312 with a diabetic foot ulcer and 111 with acute neuropathic osteoarthropathy). Median age was 70 years, median diabetes duration was 14 years and 64% were men. Of all diabetic foot ulcers, 51% were plantar and 29% were both ischaemic and deeply infected. Ulcer healing rate at 6 months significantly increased from 49% to 54% between 2008 and 2011. Management of diabetic foot ulcers varied between diabetic foot clinics: 88% of plantar mid‐foot ulcers were off‐loaded (P10–P90: 64–100%), and 42% of ischaemic limbs were revascularized (P10–P90: 22–69%) in 2011. Conclusions A unique, nationwide quality improvement initiative was established among diabetic foot clinics, covering ulcer healing, lower limb amputation and many other aspects of diabetic foot care. Data completeness increased, thanks in part to questionnaire revision. Benchmarking remains challenging, given the many possible indicators and limited sample size. The optimized questionnaire allows future quality of care monitoring in diabetic foot clinics. Copyright © 2014 John Wiley & Sons, Ltd.